Implementation of Dhuha Prayer and Yasinan in Instilling Religious Understanding of Madrasa Students In Bengkulu City - Kamila Tunnisa; Mamik Wedianti; Aziza Aryati; Nur Hidayat (Yayasan Azhar Amanaa Yogyakarta, 2025)
This study aims to describe the implementation of Dhuha prayer and Yasin recitation activities together and analyze their impact on students' religious understanding at MI Al-Baani, Bengkulu City. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. Data analysis is carried out through data reduction, data presentation, and drawing conclusions. The results show that Dhuha prayer and Yasin recitation activities are carried out routinely and structured every morning before classes begin. This activity is not only a worship routine, but also forms a religious culture within the madrasah environment. The impact is seen in increased awareness of worship, time discipline, the ability to read the Qur'an, and the growth of a sense of togetherness and spirituality in students. Supporting factors include madrasah support, the role of teachers, the religious environment, and school policies, while inhibiting factors include differences in student abilities, limited time, and the influence of the environment outside the school. In conclusion, this activity of habituating worship is effective in improving students' religious understanding comprehensively.